Using Social Media to Engage Communities with Research: SMART Social Media—Planning for Success: AEC699/WC362, 11/2020 - Lundgren, Lisa; Stofer, Kathryn A; Hecht, Kirsten; Williams, Tyus (EDIS, 2020)
This new 6-page publication of the Department of Agricultural Education and Communication focuses on developing social media plans. The intended audience is individuals (e.g., scientists wishing to share their research), organizations, or people who work on grant-funded research projects. In this article, we provide evidence-based strategies for designing, developing, and implementing social media plans to share science research with others inside and outside of the professional scientific community. While the design, development, and implementation of social media may vary, we provide general strategies that are applicable across contexts. Written by Lisa Lundgren, Kathryn A. Stofer, Kirsten Hecht, and Tyus D. Williams. This is part of a multi-part series on social media titled Using Social Media to Engage Communities with Research. https://edis.ifas.ufl.edu/wc362